PERKEMBANGAN HAMA DAN MUSUH ALAMI PADA TUMPANGSARI TANAMAN KACANG PANJANG DAN PAKCOY - Eko Apriliyanto; Bondan Hary Setiawan (Universitas Muhammadiyah Purwokerto, 2014)
The aim of this study is to know the pest population and natural enemies in intercropping of cowpea and pakchoy then its influence toward the yield. The experiment was conducted in March to August 2014 at the Polytechnique Banjarnegara field trial. The design of the research used Randomized Complete Block Design (RCBD) factorial with 4 treatment and 6 replications. Treatment plot size was 6 m x 6 m. The first factor was the spacing and the second factor was the type of fertilizer. Spacing of cowpea was 75 cm x 30 cm intercropped with pakchoy using interlinear treatment (75 cm) contained 1 pakchoy plant (J1) and 2 plant pakchoy interlinear (J2). The second factor was the provision of goat manure is 15 tonnes/ ha (P1) and the synthesis of chemical fertilizer (P2), urea 50 kg/ ha, SP36 75 kg/ ha, and KCl 25 kg/ ha, so that there were 4 treatments combinations i.e. J1P1, J1P2, J2P1, and J2P2. Analysis of the data was using the F-test, if there was any significantly different, the study was followed by Duncan Multiple Range Test (DMRT) at the 5% level. The main pests wich attacked cowpea intercropped with pakchoy were grasshoppers (Oxya sp., Fam. Acrididae), green leafhoppers (Empoasca spp., Fam Cicadellidae), caterpillars (Fam. Pyralidae), and aphis (Aphis cracivora, Fam. Aphididae). The type of intercropping (type of fertilizers and the amount of pakchoy lines) had not been able to reduce pest population on cowpea. The dominant natural enemies on the cowpea were spiders (Fam. Lycosidae) and ladybugs (Fam. Coccinellidae). The population of natural enemies along with the prey population. Intercropping types had not been able to increase the crop of cowpea (plant weight, strand number of cowpea, and cowpea weight) and also to yield of pakchoy (number of leaves, plant height, and plant weight). Keywords: pests, natural enemies, intercropping, cowpea, and pakcoy